2022
DOI: 10.1177/23259671221105471
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Symptomatic Partial-Thickness Rotator Cuff Tears: Association With Initial Tear Involvement and Work Level

Abstract: Background: Partial-thickness rotator cuff tears (PTRCTs) often progress to full-thickness rotator cuff tears (FTRCTs). Thus, it is important to analyze the risk factors for tear progression to determine the proper timing of repair. Purpose: To identify the risk factors associated with progression of PTRCT. Study Design: Case-control study; Level of evidence, 3. Methods: Included were 89 patients diagnosed with PTRCT on magnetic resonance imaging (MRI) scans who underwent nonoperative treatment at the authors’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Most patient MRIs (27 of 37) demonstrated evidence of improvement in tear morphology, with some images showing near resolution of their original RC pathology. The natural course expected is progressive enlargement for full-thickness (50% to 82.4%) and partial-thickness tears (13.5% to 26.1%) between 12- and 24-months [ 44 , 55 , 56 ]. Spontaneous improvement or resolution of rotator cuff tears as visualized on MRI is not expected, with low reported rates (4.9% to 11%) [ 44 , 55 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patient MRIs (27 of 37) demonstrated evidence of improvement in tear morphology, with some images showing near resolution of their original RC pathology. The natural course expected is progressive enlargement for full-thickness (50% to 82.4%) and partial-thickness tears (13.5% to 26.1%) between 12- and 24-months [ 44 , 55 , 56 ]. Spontaneous improvement or resolution of rotator cuff tears as visualized on MRI is not expected, with low reported rates (4.9% to 11%) [ 44 , 55 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The natural course expected is progressive enlargement for full-thickness (50% to 82.4%) and partial-thickness tears (13.5% to 26.1%) between 12- and 24-months [ 44 , 55 , 56 ]. Spontaneous improvement or resolution of rotator cuff tears as visualized on MRI is not expected, with low reported rates (4.9% to 11%) [ 44 , 55 , 57 , 58 ]. While MRI imaging alone has been shown to poorly correlate with clinically relevant pain [ 59 61 ], it is encouraging that imaging did tend to improve following BMC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the major objective of mending a torn rotator cuff is to enhance the patient's quality of life by lowering discomfort and increasing shoulder function. Strati ed rotator cuff tears are a common type of rotator cuff tear and are usually associated with more signi cant pain than full rotator cuff tears [1,2,3], resulting in limited shoulder function and, under the in uence of a variety of risk factors, can lead to an increase in the area of the rotator cuff involved in the tear, which progresses to a full rotator cuff tear [4]. Since Codman proposed the concept of "rotator cuff repair" at the beginning of the 20th century, rotator cuff repair methods have gone through the development of incision repair, arthroscopic-assisted small-incision repair, and total arthroscopic repair [5], and the literature on arthroscopic rotator cuff repair has reported that the probability of rotator cuff retears ranges from 11.4-94% in poor surgical treatment [6,7,8].…”
Section: Introductionmentioning
confidence: 99%